Unsolved Problems Treatment of Patients with Thermal Inhalation Injuries (Literature Review) - Ishnazar Boynazarovich Mustafakulov; Jurabek Ibodulloyevich Alimov; Akobir Fakhriddinovich Ergashev; Yokubjon Erkin ugli Khursanov; Khusniddin Alisher ugli Jumanov (Asian Journal of Medical Research, 2021)
Despite the achieved certain successes in the treatment of victims with combined thermal trauma, a wide arsenal of modern pharmacological agents and medical equipment, it should be recognized that the existing principles of treatment of this severe category of victims are mainly syndromic in nature, and treatment-tactical algorithms require further development, depending on the severity of damage to the respiratory system and prognostic assessment of the outcome of combined thermal injury.